Established and advanced adjuvants in vaccines' formulation: Mineral adsorbents, nanoparticulate carriers and microneedle delivery systems - Krajišnik Danina; Ilić Tanja; Nikolić Ines; Savić Snežana (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2019)
In the era of modern vaccinology, limited immunogenicity of the most commonly used antigens has enforced the use of various adjuvants in vaccine formulations to achieve desired immune response. Aluminum-containing adjuvants have been, historically, the most widely used mineral immunostimulants, generally regarded as safe to use in human vaccines. The great academic progress in inorganic (nano)materials synthesis, structure control and functionalization design has led to a growing interest in innovative adjuvants such as clays, mesoporous silica nanoparticles, zinc oxide, iron oxide and iron hydroxide nanoparticles, etc. On the other hand, there has been an intention to use specific nanoparticulated antigen delivery systems, such as nanoemulsions, in order to protect antigens from premature proteolytic degradation and/or to improve antigen immunogenicity by facilitating antigen uptake and processing by antigen presenting cells. Simultaneously, numerous research efforts have been focused on the development of innovative technologies for antigen delivery into the skin (such as microneedles), with the aim to improve vaccine efficacy alongside with enhanced patient adherence, particularly in children population (noninvasive or minimally invasive administration). Therefore, this review deals with each of these approaches in more detail, with the special emphasis on examples of their use in vaccine formulations as well as on the factors influencing their efficacy and safety.